Facile fabrication of hollow mesoporous Eu3+-doped Gd2O3 nanoparticles for dual-modal imaging and drug delivery. (December 2015) - Shi, Han-Zhu; Li, Lu; Zhang, Ling-Yu; Wang, Ting-Ting; Wang, Chun-Gang; Su, Zhong-Min
Abstract: In this paper, we report a facile and reproducible approach to prepare Eu 3+ -doped gadolinium oxide (Gd2 O3 ) hollow mesoporous nanoparticles (HMNPs) by using polyacrylic acid sodium salt (PAAS) NPs as templates. The synthesized NPs are well-dispersed with a diameter of 120 nm and a wall thickness around 20 nm, which were utilized as nanoprobes for simultaneous dual-modal fluorescence and magnetic resonance (MR) imaging and drug delivery due to their excellent luminescent property and obvious T1 -enhancement effect as well as the HM structure. The Eu 3+ -doped Gd2 O3 HMNPs possess the loading capacity for doxorubicin (DOX) as high as 310 μg mg −1 and display the pH-responsive drug release property. In vitro cell cytotoxicity tests on cancer cells verify that the DOX loaded Eu 3+ -doped Gd2 O3 HMNPs have comparable cytotoxicity with free DOX at the same concentration of DOX, while Eu 3+ -doped Gd2 O3 HMNPs alone show no obvious cytotoxicity. In addition, Eu 3+ -doped Gd2 O3 HMNPs exhibit excellent capability in dual-modal fluorescence and MR imaging. Taken together, these findings highlight the fascinating features of Eu 3+ -doped Gd2 O3 HMNPs as dual-modal imaging contrast agents and drug delivery vehicles. Graphical abstract: A novel and facile strategy is developed to fabricate Eu 3+ -doped Gd2 O3 hollow mesoporous nanoparticles, which are applied for simultaneous dual-modal MR and fluorescence imaging and anti-cancer drug delivery. Highlights: Well-dispersed Eu 3+ -doped Gd2 O3 nanoparticles were prepared by a facile method. They were employed as theranostic agents for dual-modal imaging. They can be applied for use as drug delivery carriers with high doxorubicin payload. They equipped with pH-responsive sustained release property.